Seatings : Singapore - gideon-jamie (Temporary Press, 2023)
Atelier HOKO (2002) is an independent research lab that focuses on the study of the growing disengagement between people, things and space. Founded by Alvin Ho and Clara Koh. This investigation by Gideon-Jamie in the 'Street Report' publication series looks at the seatings we observe on the streets of Singapore, some of them reinforce the notion of a seat while others challenge or expand it.
English
Keywords: N4390-5098 Visual Arts. Exhibitions; Singapore